KETERLIBATAN MASYARAKAT TERHADAP PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN LAHAN GAMBUT TELUK PAKU KECAMATAN BATI-BATI KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Viby Hendriawan; Normela Rachmawati; Fonny Rianawati (Jurnal Sylva Scienteae, 2020)
. Research assumed the title of “Community Involvement On The Prevention And Handling Peat Fire Teluk Paku In Bati-Bati Village Bati Bati Distric Tanah Laut Regency, South Borneo” Having objective of knowing the perception and participation of the community towards prevention and fire tackling peat on the gulf of spikes. Benefits from the study can inform us to the rural and become additional information in a bid to fire prevention peat that will involve society especially in the area of research locations. The motive of fire in peatlands is caused by human activities due to economic considerations. The reason for the burning of land because it is considered as the easiest way to open the land, effective and efficient.Sample selection with the census method of focus on the respondents who often actually interact with and dwell and sit among the remote and sparsely populated peat, the number of respondents in get as many as 80 people. The methodology used technique score scale 1-3-5 value a score based on set sums consisting of 4 the kinds of questions that each consisting of 5 to 6 at the present with the question. A conclusion that in get the perception of the community towards the fire prevention peat the gulf of a nail are categorized was in the middle of (1118). The perception of the community towards fire tackling peat included in a category high (1580). Level of participation of the community towards fire prevention peat categorized high (1770). Participation of the community fire tackling peat included in a category was (1348).Keywords: Peat Fire; Parception; Participation